THE IMPLEMENTATION OF AUTONOMOUS LEARNING ON ESSAY WRITING CLASS - Sahrawi, Sahrawi (STKIP PGRI Bandar Lampung, 2021)
The spread of corona virus in 2020 has an impact on various sectors in Indonesia including the world of education so that the learning system is changed to online based. Essay writing class in one of the courses that must be carried out online using an autonomous learning approach. Therefore, the purposes of this study were to know the students’ perception and the impact of the implementation of online autonomous learning in essay writing class. This research was conducted in quantitative and qualitative method. The participants in this study consisted of 36 second semester students of English education study program IKIP-PGRI Pontianak who were selected purposively. The data was obtained from questionnaire which was then randomly selected for online interview. The data was also enrich by document in the form of students’ score. The result of the study showed that the implementation of online autonomous learning is not really significant in helping students to understand materials, organize ideas or topics, helping them to be independent learner, and improving vocabulary on essay writing class. Besides, most of the students preferred face-to-face class where the teachers could guide them directly. Some students also find it difficult to find stable network. Then, the lack of detailed explanations and many assignments from the teacher make students reluctant to join the class.